Wireless Sensor Network Design based on Hybrid Tree-Like Mesh Topology as a New Platform for Air Pollution Monitoring System - Muhammad Iqbal; Muhammad Fuad; Heru Sukoco; Husin Alatas (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
In this paper, we propose a new platform for air pollution monitoring system based on wireless sensor network (WSN) with Tree-like Mesh topology. We used ZigBee device and General Packet Radio Service (GPRS) for data transfer protocol. The results of a conducted test showed a good performance in delivering data in real time mode. We found that the fewer hop produced higher throughput but lower delay and packet loss ratio. The system performance demonstrated that the reduction of one hop increased 32.06% of throughput, decreased 23.28% of delay and 0.01% of packet loss ratio.In this paper, we propose a new platform for air pollution monitoring system based on wireless sensor network (WSN) with Tree-like Mesh topology. We used ZigBee device and General Packet Radio Service (GPRS) for data transfer protocol. The results of a conducted test showed a good performance in delivering data in real time mode. We found that the fewer hop produced higher throughput but lower delay and packet loss ratio. The system performance demonstrated that the reduction of one hop increased 32.06% of throughput, decreased 23.28% of delay and 0.01% of packet loss ratio